PENGARUH SANKSI ADMINISTRASI SOSIALISASI PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PENYAMPAIAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI (Studi di Kantor Pelayanan Pajak Pratama Singosari, Kabupaten Malang) - Putra, Risky Riyanda Rama (Jurnal Mahasiswa Perpajakan, 2014)
The amount of Taxpayer is increasing year by year, unfortunately, it’s not balanced with the Tax Compliance in order to fulfil Taxpayer’s obligation. The purpose of this research to analyze the influence of Administrative Sanction, Taxation Socialization and Taxpayer Awareness toward Tax Compliance for Reporting Individual Tax Return. Based on the results regression analyze, the tax payer compliance as dependent variable and Administrative Sanctions, Socialization Taxation and Taxpayer Awareness as independent variables, obtained F-value in the amount of 35,199 and its significant level is 0,00 (less than 0,05). So it means that independent variable has a significant influence upon dependent variable. The magnitude of the partial test results are known t count variable X1 to variable Y is 2,708 this means that t count > t table      (2,708>1,984 ). The magnitude of the t count variable X2 to variable Y is 2,993 this means that t count > t table ( 2,993>1,984 ). Then the magnitude of the t count variable X3 to variable Y is 2,272 this means that   t count > t table ( 2,272>1,984 ). On the result of calculation, Adjusted R Square is 0,509. It means tax payer compliance be influenced only 50,9% by dependent variable. Keywords : Administrative Sanction, Taxation Socialization, Taxpayer Awareness, Tax Compliance